Towards adaptive e-learning among university students: by Applying Technology Acceptance Model (TAM) - Alamri, Mahdi M; Al-Rahmi, Waleed Mugahed; Yahaya, Noraffandy; Al-Rahmi,, Ali Mugahed; Abualrejal, Hussein; Akram, M. Zeki (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
E-learning is a form of education that is increasingly being used in higher education in the developed world. The aim of the study was to evaluating students’ satisfaction of e-Learning. In this research, we apply and use the theory of technology acceptance model (TAM). We employ structural equation modelling (SEM) approach with SmartPLS software to investigate students’ adoption process. Findings indicates that the perceived ease of use, perceived usefulness and intention to use e-learning among university students have a positive impact and substantially associated with learning performance and learning satisfaction. The study concludes that university students in Malaysia have positive perceptions towards e-learning and intend to practice it for educational purposes.